Non Feminity in the Protagonist of la Mujer Hombre, a Dramatic Work Written by Román Vial [No Feminidad en la Protagonista de la Mujer Hombre, Texto Dramático de Román Vial] - Rueda-Castro, J (Universidad Catolica Silva Henriquez, 2022)
In 1875, Román Vial (Valparaíso, 1833-1896) published La mujer hombre. The story shows the transvestite protagonist, in a male body with which she has achieved financial independence and socially acknowledged in the public realm. Based on the above, this paper deals with an interpretation of the main character’s expression as a gesture of subjugation related to the culturally based ruling system of the time. Besides, it provides an analysis of how the female subject within the dramatic frame of the text has been underestimated; this has been done by referring to the following aspects: a) the image of the male / father as a symbol of order; b) the denial of subjectivity taking place in female characters and of the processes that they go through; and c) the archetype of the woman dominated by passion and irrationality. © 2022 Universidad Catolica Silva Henriquez. All rights reserved.